Understanding Performance Decrements in a Letter-Canceling Task: Overcoming Habits or Inhibition of Reading - Myers, Larry; Downie, Steven; Taylor, Grant; Marrington, Jessica; Tehan, Gerald; Ireland, Michael J. (Frontiers in Psychology, 2018)
Abstract The importance of self-regulation in human behaviour is readily apparent and diverse theoretical accounts for explaining self-regulation failures have been proposed. Typically, these accounts are based on a sequential task methodology where an initial task is presented to deplete self-regulatory resources, and carryover effects are then examined on a second outcome task. In the aftermath of high profile replication failures using a popular letter-crossing task as a means of depleting self-regulatory resources and subsequent criticisms of that task, current research into self-control is currently at an impasse. This is largely due to the lack of empirical research that tests explicit assumptions regarding the initial task. One such untested assumption is that for resource depletion to occur, the initial task must first establish an habitual response and then this habitual response must be inhibited, with behavioural inhibition being the causal factor in inducing depletion. This study reports on four experiments exploring performance on a letter-cancelling task, where the rules for target identification remained constant but the method of responding differed (Experiment 1) and the coherence of the text was manipulated (Experiments 1 to 4). Experiment 1 established that habit forming and behavioural inhibition did not produce any performance decrement when the targets were embedded in random letter strings. Experiments 2 to 4 established that target detection was sensitive to language characteristics and the coherence of the background text, suggesting that participants’ automatic reading processes is a key driver of performance in the letter-e task.